Traditional Food Ordering Service Information System "ANTAR RASA" - Nashifah Nurul Fajri; A. Siti Rahmawati; Ainun Mardiah; Putri Rahayu (Journal of Digital Technology and Computer Science, 2024)
The younger generation's interest in traditional food, partly due to limited digital promotion and accessibility, raises concerns about the preservation of Makassar's culinary heritage. This research aims to design and implement AntarRasa, a web-based food ordering information system to facilitate online access to traditional foods while strengthening local cultural identity. This study uses a qualitative descriptive-analytical method, with data collected through structured interviews and user observations, then thematically analyzed and validated to ensure its accuracy and reliability. The system was developed with features including registration, login, home, about, menu, gallery, and order, and tested using white-box and black-box verification methods. The results of the study showed that the system functions effectively, meets user needs, and provides convenience in ordering traditional food. In conclusion, AntarRasa supports the preservation and promotion of culture by integrating technology with culinary heritage and can serve as a model for similar applications in the context of other regional foods.